The effect of the formation damage on the productivity in Bahi oil field - Salem Khalefah Fattouh; Najw Abdulmajid Salim Bahroun (Surman Journal of Science and Technology, 2025)
The skin effect is a crucial factor that can significantly impact the productivity of oil and gas wells. The skin effect refers to the additional pressure drop caused by the formation damage or alteration near the wellbore, which can be either positive (increased pressure drop) or negative (decreased pressure drop). By addressing the skin effect, operators can improve the overall efficiency and economics of their oil and gas operations, maximize hydrocarbon recovery and enhance the profitability of their assets. Continuous research and technological advancements in well construction, completion, and stimulation techniques are crucial for the industry to effectively manage the skin effect and optimize well productivity. In this research, damage to the study area was studied a well A1 has the highest well flowing pressure (Pwf) of 2100 psi and the highest maximum flow rate (Q max) of 9800 bbl/day without skin effects. Well A2 has the second-highest Pwf of 2450.409 psi, but the lowest Q max of 8050 bbl/day without skin effects. Well A3 has the Pwf 1620 psi and Q Max of 3600, but a significantly lower Q max of 3600 bbl./day without skin effects.